2005
DOI: 10.1007/s11661-005-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

Microsegregation in Al-Cu alloys

Abstract: A comparison has been made between the amount of microsegregation predicted by a numerical model and that found experimentally in Al-Cu alloys varying in composition between 1 and 8 wt pct Cu. A depleted region was predicted and observed experimentally near the Al 2 Cu. The depleted region was formed below the eutectic temperature and had a significant effect on the ordered compositionfraction plots, particularly for high alloy compositions. Although the fit between experiment and theory was reasonably good, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Therefore, it is important to understand the solidification sequence in these alloys, which in turn will dictate the heat treatment required thereafter to obtain the desired microstructure. Under normal conditions of solidification even though diffusion in the solid is limited, it is still appropriate to assume that equilibrium conditions exist at the solid/liquid interface [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to understand the solidification sequence in these alloys, which in turn will dictate the heat treatment required thereafter to obtain the desired microstructure. Under normal conditions of solidification even though diffusion in the solid is limited, it is still appropriate to assume that equilibrium conditions exist at the solid/liquid interface [15].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in some cases, suppression of the Class II invariant reaction, L + r fi A2 + l, might occur. [28,29] Likewise, in the Pb-Sn-Sb system during rapid cooling following nucleation and growth of primary Sb, the liquid composition approaches the Sb-Pb eutectic valley instead of the Sb-Sn eutectic valley, resulting in the (L fi Sb + Pb) eutectic reaction instead of the (L fi Sb + SbSn) eutectic reaction. [30] Both (1) and (2) will then have an important role in the subsequent invariant reactions, if these do occur, and on the subsequent three-phase reactions that result, when not all the liquid has been consumed.…”
Section: Introductionmentioning
confidence: 99%
“…It was stated previously [6,7,10] that sorting schemes based on a single selected solute with monotonously ascending or descending content may not describe the correct phase sequence during solidification. In this work, the leadingelement sort (Al) is also found to be incapable of revealing the primary precipitation of the Al 8 Mn 5 phase characteristic of the solidification of the AM50 alloy.…”
Section: B Issues Regarding Quantitative Epma Mappingmentioning
confidence: 99%
“…Numerous studies involving the X-ray mapping of directionally solidified samples and data processing are found in the literature; most deal with steel, [6,8] aluminum alloys, [1,9,10] or superalloys, [7,11] but a few are found that deal with magnesium alloys. Zhang et al [12] recently combined directional solidification (DS), EPMA, and the Scheil-solidification model to study the morphology and microsegregation of a binary Mg-4 wt pct Al alloy.…”
Section: Introductionmentioning
confidence: 99%